THE EVERYDAY LIFE OF BUREAUCRACY: SOURCE ASPECTS OF THE FUNCTIONING OF THE KHERSON CITY COUNCIL IN 1879 (Південний архів (історичні науки), 2025)
The study of local self-government in Kherson in the second half of the 19th century is becoming particularly important today due to the large-scale loss of documentary heritage caused by the Russian occupation in 2022. A significant part of the pre-revolutionary funds of the State Archives of the Kherson Region, in particular the materials of the city council, were stolen. This necessitates the introduction into scientific circulation of those sources that have been preserved in copies and private collections, which acquires not only scientific but also memorial significance. The purpose of the article is to reconstruct the administrative everyday life of Kherson in 1879 through the analysis of materials from fund No. 4 of the State Archives of the Kherson Region, which represent the activities of the city council and the administration. The research methodology is based on an interdisciplinary approach and the theory of everyday life, which allows sources to be viewed as textual representations of social order, communication practices, and authoritative discourse. The main research materials include: the Journal of the Kherson City Duma Meetings and the Memorial Book of the Kherson City Public Administration. The first document records the chronicle of the practical work of the Duma – the composition of those present, the course of discussions, and the adoption of decisions, which allows us to trace the mechanisms of the functioning of the city bureaucracy. The second summarizes the activities of the local government, providing systematic data on finances, staff, institutions, and commissions. Together, they reproduce the rhythm of city life, show the logic of decision-making, and the forms of communication between the Duma and the administration, the deputies, and the community. The regularity of meetings (mostly weekly) and the content of discussions – from economic issues to the supervision of schools and hospitals – demonstrate the establishment of a stable administrative routine. It is in these practices that the formation of local modernity is manifested, where bureaucracy acted not only as an apparatus of power, but also as a social environment of urban life. In conclusion, the analysis of the 1879 Duma documents allows us to reconstruct the social texture of Kherson’s bureaucracy and see how institutional culture, civic participation, and local identity were formed through everyday administrative work. In the context of contemporary military losses, such sources become an act of restoring the historical memory of the city and its past continuity.
Keywords: Kherson, urban self-government, everyday life, bureaucracy, archival sources, local modernity, historical memory